Parent-Child Relations A Guide to Raising Children - Altalib, Hisham (International Institute of Islamic Thought, 2013)
This easy-to-read, comprehensive guide contains what you need to know on how to parent with confidence. Packed with advice and powerful tips, using the latest research on child development and parenting techniques, it offers a mine of information on how to let children flourish, take the frustration out of parenting and develop happy family relations. Authors provide guidance on developing character, knowledge, values, and skills, as well as a faith-based outlook in children, benefitting parents with kids of all ages. The many strategies and techniques offered include: teaching children how to problem-solve, make decisions, and develop self-esteem. Raising God conscious, moral, successful children, with a sense of civic responsibility in today's world is not easy. It is also not impossible. Effective parenting is the key.